Persistent Na+ influx drives L-type channel resting Ca2+ entry in rat melanotrophs. (May 2019) - Kayano, Tomohiko; Sasaki, Yuto; Kitamura, Naoki; Harayama, Nobuya; Moriya, Taiki; Dayanithi, Govindan; Verkhratsky, Alexei; Shibuya, Izumi
Graphical abstract: Highlights: The resting [Ca 2+ ]i of rat melanotrophs was reversibly suppressed by antagonists of L-type Ca 2+ channels. The resting [Ca 2+ ]I was also suppressed by a reduction in the extracellular Na + concentration. When cells were voltage-clamped at –80 mV, lowering the extracellular Na + caused a positive shift of the holding current. mRNAs of TRPV1, TRPV4, TRPC6, and TRPM3-5 were detected with RT-PCR. The TRPV channel blocker, ruthenium red, suppressed the holding current and significantly decreased the resting [Ca 2+ ]i . Abstract: Rat melanotrophs express several types of voltage-gated and ligand-gated calcium channels, although mechanisms involved in the maintenance of the resting intracellular Ca 2+ concentration ([Ca 2+ ]i ) remain unknown. We analyzed mechanisms regulating resting [Ca 2+ ]i in dissociated rat melanotrophs by Ca 2+ -imaging and patch-clamp techniques. Treatment with antagonists of L-type, but not N- or P/Q-type voltage-gated Ca 2+ channels (VGCCs) as well as removal of extracellular Ca 2+ resulted in a rapid and reversible decrease in [Ca 2+ ]i, indicating constitutive Ca 2+ influx through L-type VGCCs. Reduction of extracellular Na + concentration (replacement with NMDG + ) similarly decreased resting [Ca 2+ ]i . When cells were champed at –80 mV, decrease in the extracellular Na + resulted in a positive shift of the holding current. In cell-attached voltage-clamp and whole-cell current-clamp configurations, the reduction of extracellular Na + caused hyperpolarisation. The holding current shifted in negative direction when extracellular K + concentration was increased from 5 mM to 50 mM in the presence of K + channel blockers, Ba 2+ and TEA, indicating cation nature of persistent conductance. RT-PCR analyses of pars intermedia tissues detected mRNAs of TRPV1, TRPV4, TRPC6, and TRPM3-5. The TRPV channel blocker, ruthenium red, shifted the holding current in positive direction, and significantly decreased the resting [Ca 2+ ]i . These results indicate operation of a constitutive cation conductance sensitive to ruthenium red, which regulates resting membrane potential and [Ca 2+ ]i in rat melanotrophs.